2006
DOI: 10.1056/nejmoa055227
|View full text |Cite
|
Sign up to set email alerts
|

Homocysteine Lowering and Cardiovascular Events after Acute Myocardial Infarction

Abstract: Treatment with B vitamins did not lower the risk of recurrent cardiovascular disease after acute myocardial infarction. A harmful effect from combined B vitamin treatment was suggested. Such treatment should therefore not be recommended. (ClinicalTrials.gov number, NCT00266487.).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

29
792
5
33

Year Published

2007
2007
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,257 publications
(859 citation statements)
references
References 38 publications
29
792
5
33
Order By: Relevance
“…21 Reinforcing this possibility, some recent large-scale studies on reducing tHcy by increasing folate intake, have failed to show any impact of this intervention on CVD risk. [7][8][9] However, renal function did not modify the association of tHcy with PWV or CIMT in our data.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…21 Reinforcing this possibility, some recent large-scale studies on reducing tHcy by increasing folate intake, have failed to show any impact of this intervention on CVD risk. [7][8][9] However, renal function did not modify the association of tHcy with PWV or CIMT in our data.…”
Section: Discussionmentioning
confidence: 72%
“…4 There is evidence showing that elevated homocysteine (tHcy) concentrations are a major risk factor for CVD, 5,6 although the etiological meaning of this finding is less clear, since recent studies indicate that lowering tHcy levels does not decrease CVD risk. [7][8][9] There are several mechanisms through which elevated tHcy may play a role in arterial disease, and one of these might be a deleterious effect of tHcy on vascular function. Elevated tHcy levels may result in vascular changes through induction of endothelial dysfunction, 10 arterial wall structural change and arterial stiffness, 11 but these associations were mostly found in persons with existing disease, familial risk, or other risk factors.…”
Section: Introductionmentioning
confidence: 99%
“…25 Other studies, however, have suggested that folic acid intervention, in the presence and absence of vitamin B 6 , does not lower the risk of recurrent cardiovascular disease or death after acute myocardial infarction. 26 This finding is mirrored in studies in which patients with vascular disease showed no decrease in the risk of major cardiovascular events after supplementation with folic acid and vitamin B 6 and B 12 . 27 Despite the many apparently beneficial effects of folate supplementation, and its low incidence of toxicity, 28 some concern has been expressed regarding the interaction between vitamin B 12 and folic acid, primarily in the elderly population.…”
Section: Cardiovascular Diseasementioning
confidence: 90%
“…About two‐thirds of these patients were included in WENBIT (the Western Norway B‐vitamin Intervention Trial), a randomized clinical trial investigating the effect of B‐vitamin treatment on CVD and mortality 15. NORVIT was a randomized clinical trial including 3749 patients hospitalized with acute myocardial infarction in the period 1998‐2002 and randomized to identical treatment protocols as in WENBIT 16. In WECAC, we excluded patients with a history of previous AF from the analyses, whereas we did not have information on previous AF among patients in NORVIT.…”
Section: Methodsmentioning
confidence: 99%